Strategy for Developing the Fertilizer Sector in Bangladesh for Sustainable Agriculture (Chemical Engineering Research Bulletin, 2010)
A strategic program for developing the fertilizer sector in Bangladesh for sustainable agriculture is presented in this paper. Based on the land utilization and likely cropping patterns in the future, the expected demands for different fertilizers such as urea, diammonium phosphate, TSP, SSP and MOP have been estimated. Considering the production capacities of different fertilizers in the country as well as the conditions of the plants against the estimated demands, Bangladesh immediately requires to add additional production capacities for urea (1122,000 tpy), SSP (960,000 tpy), Phosphoric acid (226,000 tpy, 100% P2O5), Sulfuric Acid (1000,000 tpy) and Muriate of Potash (700,000 tpy). The estimated investment for adding these capacities would be around US$ 1860 million. If these additional capacities are not built, the costs for import of different fertilizers including staple cereals would be in excess of US$ 1700 (fertilizer ≈US $ 900) million every year. If the envisaged projects for adding capacities are implemented, this will make the agriculture sustainable and less dependent on import of fertilizers.DOI: 10.3329/cerb.v13i2.3126Chemical Engineering Research Bulletin Vol.13 2009 39-46